2009
DOI: 10.1037/a0016272
|View full text |Cite
|
Sign up to set email alerts
|

Extremely selective attention: Eye-tracking studies of the dynamic allocation of attention to stimulus features in categorization.

Abstract: Humans have an extremely flexible ability to categorize regularities in their environment, in part because of attentional systems that allow them to focus on important perceptual information. In formal theories of categorization, attention is typically modeled with weights that selectively bias the processing of stimulus features. These theories make differing predictions about the degree of flexibility with which attention can be deployed in response to stimulus properties. Results from 2 eye-tracking studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 50 publications
(65 reference statements)
4
138
1
2
Order By: Relevance
“…In cognitive research, eyetracking has been proven to be an effective tool to study on-line attention (e.g., Ferreira & Clifton, 1986;Haider & Frensch, 1999;Just & Carpenter, 1984;Lee & Anderson, 2001;Rayner, 1998). In recent years, it has been successfully applied to studying selective attention in category learning in the absence of knowledge (Blair et al, 2009a;Blair, Watson, Walshe, & Maj, 2009b;Rehder & Hoffman, 2005a, 2005bRehder, Colner, & Hoffman, 2009;Watson & Blair, 2008). We now use eyetracking to study how attention is affected by prior knowledge.…”
Section: How Knowledge Might Affect Attentionmentioning
confidence: 99%
“…In cognitive research, eyetracking has been proven to be an effective tool to study on-line attention (e.g., Ferreira & Clifton, 1986;Haider & Frensch, 1999;Just & Carpenter, 1984;Lee & Anderson, 2001;Rayner, 1998). In recent years, it has been successfully applied to studying selective attention in category learning in the absence of knowledge (Blair et al, 2009a;Blair, Watson, Walshe, & Maj, 2009b;Rehder & Hoffman, 2005a, 2005bRehder, Colner, & Hoffman, 2009;Watson & Blair, 2008). We now use eyetracking to study how attention is affected by prior knowledge.…”
Section: How Knowledge Might Affect Attentionmentioning
confidence: 99%
“…Shepherd, Findlay, and Hockey (1986) demonstrated that although attending without making corresponding eye movements is possible, it is not possible to make an eye movement without shifting attention. More generally, the close link between attention and eye movements has been shown across a variety of cognitive tasks (see Liversedge &Findlay, 2000, andRayner, 1998, for reviews; also see Blair, Watson, & Meier, 2009;Blair, Watson, Walshe, & Maj, 2009). Mechanisms of attention are neurally and behaviorally coupled with eye movements.…”
Section: Using Eye Fixations To Measure Attentionmentioning
confidence: 99%
“…To address this issue, we employed eyetracking methodologies (Blair, Watson, Walshe, & Maj, 2009;Fiedler, Glöckner, Nicklisch, & Dickert, 2013;Glöckner, Fiedler, Hochman, Electronic supplementary material The online version of this article (doi:10.3758/s13423-015-0935-z) contains supplementary material, which is available to authorized users. Ayal, & Hilbig, 2012;Glöckner & Herbold, 2011;Jacob & Karn, 2003;Poole, Ball, & Phillips, 2005) and developed a novel experimental task to measure actual cheating, which we call the BJoker task.^We propose that when cheating is incentivized, dishonest individuals will pay significantly less attention to undesirable information than to desirable information.…”
mentioning
confidence: 99%